THE INFLUENCE OF PRINCIPAL MANAGERIAL ACTIVITIES, JOB SATISFACTION, AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS IN HAMPANG SUB-DISTRICT - Hartono, Budi; Sulaiman; Suhaimi (Journal of K6, Education and Management, 2019)
This study aims to determine and describe the direct/indirect effects of Principal Managerial Activities, Organizational Culture, and Job Satisfaction on the Performance of Primary School Teachers in the Hampang Sub-district. This is a survey research with data quantitatively obtained from a sample of 92 people by using questionnaires that have met the validity and reliability test requirements. Furthermore, path analysis with multiple regression methods was used to test for hypotheses. The results showed that (1) Principal managerial activities, organizational culture, and teacher job satisfaction directly affected performance by 63.5%, 35.4%, and 75.5%, respectively. (2) Principal's managerial and organizational culture directly influenced job satisfaction by 63.1%, and 51.6%. (3) Principal's managerial activities and organizational culture indirectly affected teachers' performance through job satisfaction by 47.6%, and 38.9%.